Analysis of Fuzzy Differential Equation with Fractional Derivative in Caputo Sense - Qura Tul Ain; Muhammad Nadeem; Devendra Kumar; Mohd Asif Shah (Advances in Mathematical Physics)
In this article, the dynamics of the fuzzy fractional order enzyme Michaelis Menten model are investigated. To study problems with uncertainty, fuzzy fractional technique is applied. Using fuzzy theory, the sequential iterations of the model are calculated by applying fractional calculus theory and the homotopy perturbation method. A comparison is given for fractional and fuzzy results, and the numerical findings validate the fuzzy fractional case. Using MATLAB software, the results are simulated for various fractional orders, corresponding to the provided data. The simulations demonstrate the model’s appropriateness.